Meta-Analysis The Effectiveness of Digital Learning Media on Literacy Numeracy: Implications for Education Based Technology - Luthfi Ilham Ramdhani; Soeharno Soeharno; Evi Refni; Iva Sarifah; Mahdiyah Mahdiyah (Universitas Negeri Semarang, 2024)
This study evaluates the effectiveness of digital learning media in improving numeracy literacy using a meta-analytic approach. A total of 21 relevant studies were analyzed to determine the effect sizes of various digital media, including augmented reality, website-based learning, and gamification, across different educational levels. The findings indicate that digital learning media significantly enhance students' numeracy skills, with an average effect size of 0.845. Factors such as instructional methods, material complexity, intervention duration, and types of digital media influenced the level of effectiveness. Website-based media exhibited the highest effectiveness (d = 1.48), while audiovisual and gamified media contributed positively to non-cognitive learning outcomes. This study underscores the importance of integrating digital media to advance students' numeracy literacy in the era of technology.